Penerapan Sanksi Terhadap Penjual Rokok Impor Tanpa Pita Cukai di Kota Pekanbaru Berdasarkan UU No. 39 Tahun 2007 Tentang Perubahan Atas UU No. 11 Tahun 1995 Tentang Cukai - Widi Pregiati Widi (Universitas Medan Area, 2023)
This research discusses the application of sanctions against sellers of imported cigarettes without excise stamps in Pekanbaru City and the obstacles and efforts to overcome them in implementing sanctions against sellers of imported cigarettes without excise stamps in Pekanbaru City. The type of research used is sociological/empirical legal research with a statutory and case approach. Data analysis is qualitative, drawing conclusions inductively using qualitative analysis methods. The results of the research show that the application of sanctions to sellers of imported cigarettes without excise stamps in Pekanbaru City has not been implemented properly based on the regulations on Excise, where the application of sanctions is in the form of written warnings against violators while the criminal sanctions of fines and imprisonment have not been applied. Obstacles from legal factors, law enforcement or government officials, facilities or facilities and the community. Factors that law enforcement officials should propose additional staff; it would be better for the central government to evaluate the performance of KPPBC Middle Type Customs B Pekanbaru officers, if necessary, transfers should be carried out; It would be better for KPPBC Officers of Middle Type Customs B Pekanbaru to apply fines and imprisonment to large distributors and importers.